2021
DOI: 10.1111/nup.12343
|View full text |Cite
|
Sign up to set email alerts
|

What makes a nurse today? A debate on the nursing professional identity and its need for change

Abstract: The nursing profession is a familiar profession for most people all around the world. Maybe someone has a nurse in the family or has had family who's been ill and needed a nurse. If not, people at least have seen nurses in popular TV series or will associate nursing with the most famous nurse ever, Florence Nightingale. This year, the World Health Organization and the International Council of Nurses seized

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 31 publications
3
43
0
7
Order By: Relevance
“…Professional identity among nurses refers to the individuals’ positive attitude towards the nursing profession with the intention to fully practice the nursing skills and responsibilities learned from professional training ( Hao, 2011 ). Public image and self-concept significantly contribute to the development of professional identity among nurses ( Cingel and Brouwer, 2021 ). Due to the low public image and self-concept of nursing, professional identity among Chinese nursing students is often reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Professional identity among nurses refers to the individuals’ positive attitude towards the nursing profession with the intention to fully practice the nursing skills and responsibilities learned from professional training ( Hao, 2011 ). Public image and self-concept significantly contribute to the development of professional identity among nurses ( Cingel and Brouwer, 2021 ). Due to the low public image and self-concept of nursing, professional identity among Chinese nursing students is often reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that nurses have described disrespect from their organizations and society, such as belittling comments, commands (Laminchhane & Bae, 2020), empty promises (Donahue, 2020) and comments on social media. Low salaries have been seen as discrimination and nurses have stated that one reason for this has been that people assume that nurses enter the profession because they have a calling for it (England, 2005; van der Cingel & Brouwer, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Leaders put aside ego to strive towards the collective good, creating a culture where power and hierarchy can be challenged, a key facet of transformational leadership as outlined below. However, nursing leaders may also have to address the tension between exemplifying the moral characteristics of nursing, which shape professional identity, including values like compassion and caring (van der Cingel & Brouwer, 2021), and addressing corporate institutional issues, such as trying to achieve tangible improvements in resourcing and addressing power differentials. These might include challenging the power differentials in interdisciplinary management and comparatively poorer resourcing for nursing.…”
Section: Leadership Stylesmentioning
confidence: 99%